A new species of the Liolaemus darwinii group (Iguania: Liolaemidae) from Catamarca Province, Argentina - Abdala, Cristian Simón; Díaz Gómez, Juan Manuel (Zootaxa, 2006)
We provide the description for a new species from Catamarca province, Argentina that belongs to the Liolaemus darwinii group. The new species was previously considered as a population of L. ornatus, but it can be distinguished from that species mainly because of differences on coloration pattern, and its geographic distribution, which is disjunct from the populations of L. ornatus. The new species is characterized for having males with a dorsal background coloration of light brown to ferrous red, the head darker than the rest of the body, paravertebral markings rounded and never in contact, dorsolateral strips lightly marked, small dark brown spots on the throat, and a belly that is white or light red.